Incidental gallbladder cancer detected during laparoscopic cholecystectomy: conversion to extensive resection is a feasible choice - Zeng, Di; Wang, Yaoqun; Wen, Ningyuan; Lu, Jiong; Li, Bei; Cheng, Nansheng (Frontiers in Surgery, 2024)
Background Re-resection is recommended for patients with incidental gallbladder carcinoma (iGBC) at T1b stage and above. It is unclear whether continuation of laparoscopic re-resection (CLR) for patients with intraoperatively detected iGBC (IDiGBC) is more beneficial to short- and long-term clinical outcomes than with conversion to radical extensive-resection (RER). Methods This single-centre, retrospective cohort study of patients with iGBC was conducted between June 2006 and August 2021. Patients who underwent immediate reresection for T1b or higher ID-iGBC were enrolled. Propensity score matching (PSM) was used to match the two groups (CLR and RER) of patients, and differences in clinical outcomes before and after matching were analyzed. Result A total of 102 patients with ID-iGBC were included in this study. 58 patients underwent CLR, and 44 underwent RER. After 1:1 propensity score matching, 56 patients were matched to all baselines. Patients in the RER group had a lower total postoperative complication rate, lower pulmonary infection rate, and shorter operation time than those in the CLR group did. Kaplan-Meier analysis showed that the overall survival rate of patients who underwent CLR was significantly lower than that of patients who underwent RER. Multivariate analysis showed that CLR, advanced T stage, lymph node positivity, and the occurrence of postoperative ascites were adverse prognostic factors for the overall survival of patients. Conclusion Patients with ID-iGBC who underwent RER had fewer perioperative complications and a better prognosis than those who underwent CLR. For patients with ID-iGBC, conversion to radical extensive-resection appears to be a better choice.